2016
DOI: 10.5455/ijmsph.2016.09122015290
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial, demographic, educational and health characteristics of street children - a qualitative study

Abstract: Background: More and more children are being pushed on the street for various reasons. Children "on" and "of the street" continue to languish at the fringes of society. They will continue to do so unless we wake up to the harsh reality that the phenomenon of street children does not exist only in numbers; it is evident in myriad colors of deprivation and poor physical and psychological health. Programs and strategies to address their condition are not effectively implemented due to lack of information in Jammu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Similarly, the qualitative study identified challenges faced as lack of access to services such as health, education and recreation, psychological restlessness, depression, anxiety, bad feelings about self and others; and several psychosocial aspects as major challenges. Analogous to this study, a prior study showed that street children face infinite challenges (Mahderehiwot, 2014).Another study also suggested there was an apparent lack of organized health and social service for street children (Ayub, Kumat and Shora, 2015). This study therefore is consistent with these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the qualitative study identified challenges faced as lack of access to services such as health, education and recreation, psychological restlessness, depression, anxiety, bad feelings about self and others; and several psychosocial aspects as major challenges. Analogous to this study, a prior study showed that street children face infinite challenges (Mahderehiwot, 2014).Another study also suggested there was an apparent lack of organized health and social service for street children (Ayub, Kumat and Shora, 2015). This study therefore is consistent with these findings.…”
Section: Discussionsupporting
confidence: 88%
“…[15] Many health-related problems were found in studied street children most commonly 60.67% had pallor and 40% had respiratory infection followed by others. Various other studies done in India by Berad et al, in Khammam City of Andhra Pradesh, [15] in Jammu, [16] and the study in other countries such as Kenya, [17] Nepal, [9] and Awassa (Southern Ethiopia) [18] have given slightly different prevalence rate of respiratory disease and condition such as anemia which can be because of different geographical condition and availability of health services. Our study shows that around 34% of children were using tobacco products such as gutkha, cigarettes, and bidi, which is well evident in other study done in Dharan (Nepal) by Thapa et al [9] Our study shows a prevalence of 66% of malnourished street children according to BMI Z score.…”
Section: Discussionmentioning
confidence: 99%
“…Results of study revealed that, anemia, jaundice, liver problems, kidney disorder, tuberculosis, trauma, musculoskeletal pains and dermatological problems were common health problems among street children. A qualitative study on street children of Jammu and Kashmir by Ayub (2015) [7] revealed that almost all of the street children suffered from common morbidities such as respiratory problems, gastrointestinal problems, fever, injuries, and dental problems. Sharmila and Kaur (2013) [52] in their study revealed that street children of Delhi suffered from many illnesses due to their poor living conditions.…”
Section: The Health Conditions Of Street Children In South and Southe...mentioning
confidence: 99%